Imperial Policy and Changed Composition of the Auxilia: The «Change in A.D. 140» Revisited - Waebens, Sofie (Chiron. Mitteilungen der Kommission für Alte Geschichte und Epigraphik des Deutschen Archäologischen Instituts, 1970)
In 140 AD, the privileges of the auxiliary veterans were reduced, as their military diplomas attest. Before 140, the soldiers themselves, their children and descendants were granted citizenship upon discharge. At the latest by 13 December 140 (RMD I 39), however, only the children born before or after their fathers’ military service, i.e., from a legal Roman marriage, were eligible for the grant of citizenship. Fleet veterans continued to receive the civitas liberorum privilege after 140. Many scholars have wondered about the objective of this so-called «change in 140», proposing various theories, most recently Peter Weiss. Although he convincingly argued that the withdrawal of the civitas liberorum privilege from auxiliary veterans fits in with Pius’ personality and new imperial representation, in which Roman citizenship and marriage played key roles, there must have been an incentive for the introduction of the «change in 140», a problem that is explored in this paper.